Strategies and checklist for designing and conducting palliative care research with family carers: EAPC international expert elicitation study. (January 2023) - Hudson, PL; Gardiner, C; Alvariza, A; Nicholas Dionne-Odom, J; Öhlén, J; Carduff, E; Harding, R; Witkamp, E; Payne, S
Background: Palliative care services seek to improve the wellbeing of family carers of people living with serious and life-limiting illness. To help achieve this goal, systematic reviews have recommended priority areas for family carer research and the need to improve the quality of study design. Policy makers have also advocated for enhanced family carer support. However, there are specific methodological considerations and challenges in designing and conducting carer research conducted during the course of the serious illness trajectory and in bereavement. Aim: To develop strategies to improve the design and conduct of research with family carers. Design: Expert elicitation study using an adapted version of the 'Identify, Discuss, Estimate and Aggregate' elicitation protocol, supplemented with strategies from peer-reviewed literature. Setting/participants: Nine members of the management committee of the European Association for Palliative Care's Reference group on family carer research, comprising international senior research academics in family caregiving. Results: A compilation of recommended strategies and checklist was created to: (a) help researchers plan research involving family carers focussing on: preparation, conduct and dissemination and (b) assist ethics committees and funding bodies to evaluate proposals. Conclusions: The strategies and checklist for conducting research with family carers may enhance methodologically rigorous research. Consequently, researchers, practitioners and policy makers will not only gain a more comprehensive understanding of the unmet needs of family carers but also promote the development of empirically sound interventions.